2012
DOI: 10.1111/j.1600-0854.2011.01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxin Pores Endocytosed During Plasma Membrane Repair Traffic into the Lumen of MVBs for Degradation

Abstract: Cells permeabilized by the bacterial pore-forming toxin streptolysin O (SLO) reseal their plasma membrane in a Ca2+-dependent manner. Resealing involves Ca2+-dependent exocytosis of lysosomes, release of acid sphingomyelinase and rapid formation of endosomes that carry the transmembrane pores into the cell. The intracellular fate of the toxin-carrying endocytic vesicles, however, is still unknown. Here, we show that SLO pores removed from the plasma membrane by endocytosis are sorted into the lumen of lysosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 40 publications
2
86
0
Order By: Relevance
“…At lower bacterial densities and toxin concentrations, such as might be encountered during colonization or early stages of infection, host cells can detect PFT activity at the membrane, activate signaling pathways that promote survival, and initiate membrane repair. Lipid metabolism, vesicle trafficking, calcium or potassium signaling, and mitogen-activated protein kinase pathways have all been implicated in such responses (14,15,(35)(36)(37)(38). It was recently recognized that cellular blebbing may represent an additional early defense mechanism for eukaryotic cells (14,16,37,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At lower bacterial densities and toxin concentrations, such as might be encountered during colonization or early stages of infection, host cells can detect PFT activity at the membrane, activate signaling pathways that promote survival, and initiate membrane repair. Lipid metabolism, vesicle trafficking, calcium or potassium signaling, and mitogen-activated protein kinase pathways have all been implicated in such responses (14,15,(35)(36)(37)(38). It was recently recognized that cellular blebbing may represent an additional early defense mechanism for eukaryotic cells (14,16,37,39).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently recognized that cellular blebbing may represent an additional early defense mechanism for eukaryotic cells (14,16,37,39). Such membrane blebs may promote survival by physically sequestering PFT and/or receptors and may also activate distinct cellular signaling pathways that promote healing of membrane wounds (14,27,35).…”
Section: Discussionmentioning
confidence: 99%
“…Note that during the oligomerization step, some PFTs remain associated with their receptor, whereas others have already disassociated at this point. machinery, targeted to lysosomes for degradation (327). S. aureus alpha-toxin also enters cells via endocytosis, is transported via late endosomes, and then disappears from the cells.…”
Section: Figmentioning
confidence: 99%
“…Subsequently, in both cases, ASMase hydrolyzes sphingomyelin (SM) into ceramide (14,15). Ceramide self-associates in plasma membrane microdomains that bud into cells, generating endosomes that induce endocytosis (16). These results indicated that the cleavage of sphingomyelin by secreted ASMase generates ceramide-enriched microdomains in the plasma membrane, promoting endocytosis (14)(15)(16).…”
mentioning
confidence: 81%
“…Ceramide self-associates in plasma membrane microdomains that bud into cells, generating endosomes that induce endocytosis (16). These results indicated that the cleavage of sphingomyelin by secreted ASMase generates ceramide-enriched microdomains in the plasma membrane, promoting endocytosis (14)(15)(16). It is as yet unknown whether the activation of ASMase is related to the uptake of C2 toxin in target cells.…”
mentioning
confidence: 95%